PROFILE OF CRITICAL THINKING SKILLS OF STUDENTS IN CLASS VII SMP ON FRACTION ADDITION MATERIAL IN TERMS OF GENDER - Amelia, Reski; Alfisyahra, Alfisyahra; Idris, Mustamin; Lefrida, Rita (Universitas Sembilanbelas November Kolaka, 2024)
This study aims to obtain an overview of the critical thinking skills of male and female students in class VII A SMPN 9 Palu on fraction addition material. This research aims to: 1) to obtain a description of the critical thinking ability of male students on the addition and subtraction of fractions 2) to obtain a description of the critical thinking ability of female students on the addition and subtraction of fractions. This type of research is descriptive using a qualitative approach. The subjects of this research were 2 students taken from 31 students of class VII A SMPN 9 Palu consisting of 1 male student with high mathematics ability and 1 female student with high mathematics ability. The results of this study showed that male and female subjects with high mathematics ability were able to fulfill the indicators of critical thinking ability by Facione (2015), namely: (1) can interpret the problem by identifying the information known and asked appropriately and able to interpret and understand the symbols contained in the problem, (2) connect between statements, questions and concepts by making mathematical modeling appropriately (3) determine and use the right strategy in the calculation process so as to find the right final solution, (4) able to draw conclusions from what is asked in the problem, and (5) have the awareness to re-examine the solution of the problem given by identifying errors in determining the strategy or in the calculation process and then being able to believe the answer. Penelitian ini bertujuan untuk memperoleh gambaran kemampuan berpikir kritis siswa laki-laki dan perempuan kelas VII A SMPN 9 Palu pada materi penjumlahan pecahan. Jenis penelitian ini adalah deskriptif dengan menggunakan pendekatan kualitatif. Subjek penelitian ini adalah 2 orang siswa yang diambil dariÂ 31 siswa kelas VII A SMPN 9 Palu yang terdiri dari 1 orang siswa laki-laki berkemampuan matematika tinggi dan 1 orang siswa perempuan berkemampuan matematika tinggi. Hasil penelitian ini menunjukkan bahwa subjek laki-laki dan perempuan berkemampuan matematika tinggi mampu memenuhi indikator kemampuan berpikir kritis oleh Facione (2015), yaitu : (1) dapat menginterpretasi masalah dengan mengidentifikasi informasi yang diketahui dan ditanyakan dengan tepat serta mampu memaknai dan memahami simbol yang terdapat di soal, (2) menghubungkan antara pernyataan, pertanyaan dan konsep-konsep dengan membuat pemodelan matematika dengan tepat (3) menentukan dan menggunakan strategi yang tepat dalam proses perhitungan sehingga mampu menemukan solusi akhir yang tepat, (4) mampu menarik kesimpulan dari apa yang ditanyakan pada soal, dan (5) memiliki kesadaran untuk memeriksa kembali penyelesaian soal yang diberikan dengan mengidentifikasi kesalahan dalam menentukan strategi maupun pada proses perhitungan serta kemudian mampu meyakini jawabannya.